The Financial Burden of Antiquated Laws: The Case of Massachusetts' Parental Involvement Law for Abortion - Allison L. Gilbert; Isabel R. Fulcher; Alischer A. Cottrill; Elizabeth Janiak (Women's Health Reports, 2021)
Background: A majority of U.S. states enforce parental involvement laws that require minors seeking abortion to obtain parental consent, or else obtain judicial bypass through the court system. Although such laws are widespread, the financial cost of their enforcement has yet to be documented. Methods: We used data from a retrospective observational cohort study among adolescents (aged ?17 years old) who sought abortion services at Planned Parenthood League of Massachusetts (PPLM) between 2010 and 2016. We assessed the direct financial burden of judicial bypass among 449 minors accounting for direct public legal costs, private professional costs, cost of lost school, and cost to the young person. Results: The total added cost of judicial bypass in our cohort amounted to $374,982.04 (median cost of $705.14 per abortion). The direct out-of-pocket cost amounted to $84,370.23 ($179.89 per abortion). The majority of this cost was due to increased average procedure costs solely due to delays in care incurred by judicial bypass (range $0 to $5,200.50). In total, 74% of minors in our cohort were insured through Medicaid at the time of their abortion. Additional out-of-pocket costs for bypass were 20.2% of their household's maximum monthly income. Conclusions: These analyses show that judicial bypass as a function of parental involvement laws correlates with increased costs to individual minors and to the public, with the heaviest burden placed on minors of low socioeconomic status.